The influence of remote learning environment and use of technology on university students' behavioural engagement in contingency online learning - Katerina Dvorakova; Jaroslav Emmer; Renata Janktová; Kateřina Klementová (Universidad de Deusto, 2023)
The shift of instruction imposed on higher education institutions by the pandemic-related restrictions bolstered the interest in students' online class participation. This study investigates university students' engagement in remote foreign language classes during the COVID-19 lockdown. While engagement is a multi-faceted construct, we only aim to explore its behavioural dimension. The authors felt compelled to acknowledge and comprehend their students' behaviour in contingency online learning (COL). Through a qualitatively oriented exploratory case study, we sought to answer two research questions related to the extent the use of technical equipment and remote physical environment influenced students' engagement. The study was conducted with students enrolled in regular, in-person Bachelor's or Master's degree courses to qualify as teachers of English at primary or lower-secondary schools. The results indicate that the use of technology did not prove to be a significant obstacle to online learning engagement. Concerning the remote physical environment, the learning process was compromised most significantly by the intimate character of the home-working space. We believe that our findings will help educators to rationalise their expectations and formulate best practice recommendations. Received: 7 January 2022 Accepted: 16 January 2023